REALISTIC MATHEMATIC WORKSHEET BAGI GURU-GURU SEKOLAH DASAR - Ratni Purwasih; usman Aripin; Fifiet Dwi Tresnawati Santana (STKIP Persada Khatulistiwa Sintang, 2019)
the purpose of this service is to equip CCI IT elementary school teachers to be able to design learning in the classroom using instructional media. The learning media used are realistic mathematical worksheets based on geogebra softwares. LKS is one of the learning tools that must be compiled by the teacher as teaching material that supports the quality of learning. Worksheets that are equipped with visualization of images and students construct their own mathematical concepts through geogebra softwares make abstract concepts more concrete. There is also the purpose of this dedication is to provide training and mentoring to elementary teachers of IT CCI to create ICT-based worksheets and teaching materials assisted by geogebra softwere. This training is a presentation of material related to the demonstration of the use of geogebra softwares for 3D space building concepts and their applications. The next activity is assistance to training participants by dividing up several groups to facilitate further training. Based on the results of the questionnaire satisfaction of 26% increase in the ability of participants from before the training. All participants seemed very enthusiastic in participating in the training program. This can be seen from the presence of all participants starting from the beginning of the activity until the end of the activity. Participants are able to create learning media that construct student’s ability to understand 3D concept